Enhancing Learning Outcomes in Creative Products and Entrepreneurship Through Problem-Based Learning at Class XI APHP 2 - Efi Setianingsih; Cahyana Nursidiq; Anita Rinawati (Universitas Terbuka, 2025)
This study aims to determine whether the Problem-Based Learning (PBL) method can improve the learning outcomes of Grade XI APHP 2 students at SMK Negeri 1 Puring. The research design employed classroom action research intended to enhance teacher performance and student learning outcomes. The subjects of this study were 36 students of Grade XI APHP 2. Data collection took place from September 19 to October 10, 2024, over two learning cycles or four sessions. In the first cycle, student mastery was only 61.12% with an average score of 75.389. In the second cycle, the number of students achieving the Minimum Mastery Criteria (MMC) increased to 75%, with an average score of 77.827. Thus, it can be concluded that the PBL model can improve student learning outcomes in the Creative Products and Entrepreneurship subject for Grade XI APHP 2 students at SMK Negeri 1 Puring